Development of integrated science teaching module Pamekasan's local potential for training students' collaboration skills - Sufiyah, Faela; Wijaya, Bagus Rahmad (CAHAYA PENDIDIKAN, 2024)
Collaboration skills are one of the demands of the 21st century that are needed to face the development of the times. In fact, collaboration skills are still not widely applied in schools, including at SDIT Al Irsyad Al Islamiyah. The school has not integrated collaboration skills for several reasons, namely not having a deep understanding of collaboration skills and having constraints in conditioning students in groups. Therefore, an interesting learning scenario is needed that can combine practical activities, local potential, and collaboration skills. The development of a teaching module that integrates Pamekasan's local potential is carried out in order to help students practice their collaboration skills so as to produce a valid and effective teaching module. In this study, the model used was 4D (without dissemination) with interviews, questionnaires, and observations as data collection techniques. The results of the study showed that the teaching module was declared valid with a teaching module validation percentage of 96%, material validation of 83%, language validation of 83%, and validation of learning practitioners of 97%. The teaching module was also declared effective because it was reviewed from the increase in observation results at the third meeting which showed collaboration with a score of 84%, student learning outcomes were categorized as very good, namely 93%, and teacher responses obtained a score of 100% with a very good category.